Feed Choice Led to Higher Protein Intake in Broiler Chickens Experimentally Infected With Campylobacter jejuni - Visscher, Christian; Klingenberg, Linus; Hankel, Julia; Brehm, Ralph; Langeheine, Marion; Helmbrecht, Ariane (Frontiers in Nutrition, 2018)
In 2016, Campylobacter was the most commonly reported gastrointestinal bacterial pathogen in humans in the European Union with 246,307 reported cases. Of these cases, 83.6% were Campylobacter jejuni. The objective of the present study was to investigate to what extent an infection with Campylobacter jejuni alters the feed intake behavior of broiler chicks in terms of protein intake. This was done to see if, conversely, measures of control could be derived. In total, 300 commercial broilers of the Ross 308 line were allocated to four different groups, including five replications of 15 chickens each. In two groups, a conventional diet (216 g CP/kg dry matter [DM]) and in the two choice diet groups, diets with different levels of crude protein (109 g CP/kg DM and 286 g CP/kg DM, respectively) were fed between day 14 and day 42. An intake of both choice diets at a ratio of 1:1.5 resulted in a composition of consumed feed identical to that of the control concerning composition, energy and nutrient content. One group of each feeding concept was infected artificially with Campylobacter jejuni at day 21 by applying an oral Campylobacter jejuni-suspension containing 5.26 ±0.08 log10 colony forming units of Campylobacter jejuni to three out of 15 chickens. No significant differences concerning Campylobacter jejuni prevalence and excretion could be seen. Broilers infected with Campylobacter jejuni chose a higher amount of the high protein choice diet in comparison to Campylobacter jejuni negative broilers. This resulted in a significantly (p < 0.0001) higher content of crude protein in the consumed diet (198±3.09 g CP/kg DM and 208±8.57 g CP/kg DM, respectively). Due to Campylobacter jejuni infection, a significant increase in crude mucin in excreta at day 42 was seen in experimentally infected groups (62.6 ±4.62 g/kg DM vs. 59.6 ±6.21 g/kg DM, respectively; p = 0.0396). There were significantly deeper crypts in infected birds (256 ± 71.6 vs. 234 ± 61.3 µm). In summary, Campylobacter jejuni infections significantly alter the feed intake behavior of broiler chickens regarding higher protein intake. Therefore, targeted manipulation of protein supply could be tested for limiting the spread of infection.